Plastics in corrosion resistant applications - Wong, Joon Fatt; Azman, Hassan; Chan, Jia Xin; Siti Maznah, Kabeb (Elsevier Ltd, 2022)
Epoxy, alkyd, acrylic, and polyurethane are plastic materials that suitable for corrosion-resistant coatings to protect metals from rusting, as they resist most of the chemicals and exhibit excellent adhesion towards metal surfaces, which act as the barrier towards corrosion initiators. However, they have limitations in the aspect of mechanical strength, permeability, or solvent resistivity in some cases. Nanofillers are incorporated into the coatings for higher barrier properties with excellent abrasion resistance against corrosion. Advance development is desired to produce self-healing coatings for long-term protection, as well as coatings with low cost and ease in fabrication.